ANALYSIS OF THE IMPLEMENTATION OF BEHAVIORAL ACCOUNTING ASPECTS AND UNDERSTANDING OF THE VILLAGE FUNDS ALLOCATION (ADD) IN KAWISTOLEGI VILLAGE KARANGGENENG SUB-DISTRICT, LAMONGAN DISTRICT - Firda Kusumawati; Nur Ika Mauliyah (Universitas Islam Balitar, 2020)
Village Fund Allocation (ADD) is an equalization fund received by regions in the Regional / District (Regency) APBD which is distributed proportionally to each village with a minimum proportion of 10% (ten percent) after deducting the Special Allocation Fund (DAK). This research aims to determine (1) The implementation of the accounting aspects of ADD management behavior in Kawistolegi Village (2) The government's understanding of ADD management in Kawistolegi Village. This study uses a qualitative method with a descriptive approach, data collection using observation, interview and documentation techniques. Data analysis used data reduction, data presentation, and data verification. The results showed that the application of behavioral accounting aspects in ADD management cannot be said to be good overall, in some aspects of the behavior of the Village Government still needs to be improved such as aspects of accountability, control and reporting requirements. The understanding of the Village Government in managing ADD, cannot be said to be good as a whole, where at the planning and accountability stages it has been carried out in accordance with the provisions, but at the implementation stage, administration and reporting are not fully in accordance with the determined provisions.